A existência e os atributos de Deus segundo a filosofia tomista de Garrigou-Lagrange (1877-1964) - Brustolin, Filipe Luís (2023)
The subject of this dissertation is the existence as well as the attributes of God as they are conceived in the Thomistic philosophy of Reginald Garrigou-Lagrange (1877-1964). The problem leads to verify the possibility of philosophically proving the existence of God and his attributes through reason alone, without using theological premises. Since the general objective is to provide a satisfactory answer to the problem, three specific objectives are expected to be achieved. First, analyze the first principles on which the Thomistic metaphysics and, consequently, the arguments for the existence of God are based, presenting Lagrange’s defense of these principles in the face of modern-contemporary criticism; the principles are those of non-contradiction or identity, sufficient reason, efficient causality, and finality. Second, investigate, according to Lagrange’s Thomism, how is it possible for the human intellect to achieve, philosophically, a natural knowledge about the existence of God: ascending from the beings of reality through the five ways: from movement, efficient causality, ontological contingency, gradation of perfections, and cosmological order. Third, ascertain which are the attributes of God, since there is between the self-subsistent Being (ipsum Esse subsistens) and the beings caused by him a relation of analogy (that rejects both the univocity and the equivocity of being), through which, by negating or maximizing the attributes belonging to the latter, one can know the attributes of the former. Then philosophically enumerate the attributes relative to the being of God: unity, simplicity, truth, perfection, goodness, infinity, immensity, ubiquity, immutability, eternity, invisibility, incomprehensibility, and knowableness; and those relative to God’s operations: wisdom, foreknowledge, providence, will, love, justice, mercy, and omnipotence. Finally, establish what is the relation that lies between the divine essence and the divine attributes, namely: the identification of God’s attributes with each other and with his own essence, which, however, does not make the attributes synonymous, since, even though in God the attributes are identified with each other, distinct realities in caused beings analogically correspond to them; therefore, in the human way of understanding, there is a virtual distinction between the divine attributes. The research is based on the path proposed by Lagrange in “God, his existence and his nature: a Thomistic solution of certain agnostic antinomies” (1914), work that systematizes his natural theology. Necessary references are made to other works of Lagrange and to Thomas Aquinas; lastly, an opportune contribution comes from both comments on the subject written by other contemporary Thomists, and commentators that write on Lagrange himself.